High‐anthocyanin strawberries through cultivar selection. (6th August 2012) - Fredericks, Charissa H; Fanning, Kent J; Gidley, Michael J; Netzel, Gabriele; Zabaras, Dimitrios; Herrington, Mark; Netzel, Michael
Abstract BACKGROUND: Diets high in fruit and vegetables are known to have significant health benefits. This is in part due to the presence of phytochemicals, which possess potential protective health benefits. This study focuses on the ability of strawberries to be bred for higher anthocyanin content. This is a major contributor to the characteristic colour and nutritional value of ripe strawberries, together with phenolic acids, ascorbic acid and total antioxidant capacity. RESULTS: Anthocyanins in five commercial strawberry cultivars and three breeding lines were assessed. This led to the discovery of one breeding line (BL 2006‐221) as an exceptional source of anthocyanins (∼1 g kg−1 fresh weight), with approximately double the levels of current commercial cultivars. Temperature was shown to influence anthocyanin extraction, with 40 °C being the best extraction temperature using the accelerated solvent extraction (ASE) method. Hue angle and anthocyanin concentration showed a good correlation (r2 = 0.69). CONCLUSION: The new breeding line BL 2006‐221 has the potential to be used in the development of phytochemically rich strawberry cultivars. Using hue angle as a screening tool for total anthocyanin concentration and extraction of anthocyanins from strawberries by ASE at 40 °C would support such cultivar development. © 2012 Commonwealth of Australia